151k views
1 vote
Please help me to do this problem can you give me some explain about how to find the answer.

Please help me to do this problem can you give me some explain about how to find the-example-1
User Rjd
by
5.6k points

1 Answer

2 votes

To find the value of the expression given we need to remember that following properties:


\begin{gathered} a^(-n)=(1)/(a^n) \\ (1)/(a^(-n))=a^n \end{gathered}

Using this properties, we can find the value of the expression. To do this we plug the values of x and y given:


\begin{gathered} (1)/(2^(-2)(2)^(-3)(-4)^5)=(2^2(2)^3)/((-4)^5) \\ =(4\cdot8)/(-1024) \\ =-(32)/(1024) \\ =-(1)/(32) \end{gathered}

Therefore the answer is C.

User Doogal
by
5.0k points